(untitled) (Research, Society and Development, 2020)
Objective: To know the knowledge and practices of people with type 2 diabetes mellitus about diabetic foot. Methodology: Field research, qualitative, exploratory and descriptive. Data collection carried out between April and August 2016 at the home of eight people with type 2 diabetes mellitus, through narrative interview recorded on audio. For the analysis of the data the operative proposal was used. Results: Two units of meaning were identified: “I have never heard of / Worse is that I knew”: the knowledge about the diabetic foot and “I take care of my feet a lot”: the care practices. The data revealed the ignorance of some participants, however, those who knew, lived with some complication of diabetes mellitus or had a family member with diabetic foot. The care practices identified were hygiene, hydration of the feet, checking for possible cracks and / or wounds. Learning in relation to practices took place through health professionals and educational strategies. Conclusions: It is necessary for nurses to know the knowledge and practices about the diabetic foot of people with type 2 diabetes mellitus to develop health promotion measures, through health groups and / or nursing consultations, according to individuality of each person.